2012
DOI: 10.1155/2012/927132
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Rhodamine B with H3PW12O40/SiO2Sensitized by H2O2

Abstract: In order to remove aquatic organic dye contaminants by utilizing the inexpensive and inexhaustible solar energy, the Keggin-type H3PW12O40was loaded on the surface of SiO2with the sol-gel method and sensitized by H2O2solution. The photocatalytic degradation of rhodamine B (RhB) by H3PW12O40/SiO2(x) under simulated natural light irradiation was investigated. The effects of the initial RhB concentration, the solution pH, and catalyst dosage on the photocatalytic degradation rate of RhB were also studied. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Some studies indicated that an increase in photocatalyst dosage could result in increasing the photocatalytic efficiency (Yang et al, 2012). Therefore, an increase in the photocatalyst dosage does not always lead to the enhancement of photocatalytic activity (Hua et al, 2014; Wang, Huang & Yang, 2010; Yang et al, 2012). An excessive dosage increase, however, may decrease the photocatalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies indicated that an increase in photocatalyst dosage could result in increasing the photocatalytic efficiency (Yang et al, 2012). Therefore, an increase in the photocatalyst dosage does not always lead to the enhancement of photocatalytic activity (Hua et al, 2014; Wang, Huang & Yang, 2010; Yang et al, 2012). An excessive dosage increase, however, may decrease the photocatalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…An excessive dosage increase, however, may decrease the photocatalytic efficiency. It seems that surplus photocatalyst results in scattering the photons in the solution and decreasing the photons that reach the surface of photocatalyst (Feng & Shang, 2012; Xu et al, 2012; Yang et al, 2012). Some other researchers reported the same results for various composites (Feng & Shang, 2012; Wei et al, 2012; Xu et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] Furthermore, the photocatalytically active sites are blocked, which results in a reduction in the interaction of photons. [20, 3031] By using the Langmuir–Hinshelwood kinetic model the reaction parameters were determined by Equation (2):[30, 32]…”
Section: Resultsmentioning
confidence: 99%